A numerical model to investigate non-gray photothermal characteristics of paraffin-containing glazed windows. (December 2019) - Li, Dong; Wang, Baichao; Li, Qing; Liu, Changyu; Arıcı, Müslüm; Wu, Yangyang
Highlights: Photothermal dynamic characteristics of paraffin-containing glazed windows were studied. Numerical model was upgraded including non-gray characteristics of glass and paraffin. Solid and liquid phase of paraffin were spectrum selective. Effects of different melting points and thicknesses of paraffin were analyzed. Solar transmittance and transmitted energy were investigated. Abstract: Most of numerical methods developed for the photothermal transfer researches of the paraffin-containing glazed windows adopt the gray-body model, in which the spectrum properties of glass and paraffin are generally not taken into account, even though scholars are aware of the fact that glass and paraffin are spectrum selective. Therefore, in this work, a one-dimensional photothermal model that accounts phase dependent thermophysical properties and spectrum dependent optical properties was developed based on the finite difference method, which is utilized to study the heat transfer through the glazed units incorporating paraffin. The results of the established model including non-gray characteristics of glass and paraffin with different spectrum bands were compared with the experimental results in terms of transmittance and temperature. It was observed that 4-band spectrum can accurately simulate the heat transfer process. Then, the photothermal performance of the double-layer glazed windows was studied with the verified model for different melting temperatures of paraffin under summer conditions and paraffin layer thicknesses under both summer and winter conditions, and the transmitted energy from the window units for the considered parameters was quantified. The results showed that inappropriate selection of melting temperature or paraffin layer thickness may defeat the purpose of energy saving. For the studied climatic conditions, the photothermal performance of the paraffin-containing glazed window is better when the melting point of paraffin was 18–26 °C, and the recommended paraffin layer thicknesses is 6–12 mm considering the transmitted energy.